Nonlinear actuation of non-prismatic dielectric elastomeric membrane. Issue 1 (2nd January 2021) - Tewary, Moumita; Roy, Tarapada
ABSTRACT: Nowadays, the soft material, dielectric elastomers (DEs) are being used for many engineering applications due to their exceptional properties like high strain rate sensitivity, low power consumption, capable of static force measurement and capability of changing dimensions when subjected to voltage. They have the ability of converting mechanical energy to electrical energy and vice versa. In this article, nonlinear dynamic behavior of viscoelastic tapered DE under mechanical and electromechanical loading is studied. A dynamic model based on standard linear solid model is incorporated for viscoelasticity. Strain energy density of the system is derived from Gent model of hyperelasticity. The tapered DE is analyzed with different values of damping coefficients, ratio of shear moduli of springs, width and height tapers. The effects of tapers greatly put an impact on the dynamic responses of the system. The tapered DEs exhibits damped vibration and weak nonlinearity with an increase in damping force. The dynamic stability of tapered DEs is also studied using phase diagrams, and the results indicated that with an increase in damping force, the dynamic stability changes from a state of aperiodic vibration to quasi-periodic vibration. It is also found that the resonant frequency and peak amplitude reduce with an increase in the damping force.